A Case Study of English Teaching Methods at SMK Muhammad Yaasiin Sei Lepan - Muhammad Hassan; Fernando de Napoli (LPPM STKIP AL MAKSUM, 2021)
Teaching English to young learners in many schools is not somethingnew. Although English has been taught for many years, the fact showsthat the process of teaching English does not always get good result.The English language teaching and learning often face problems. Inthis case, strategies of teaching English are purposed to the way ofteaching English in practicing. In SMK Muhammad Yaasiin SeiLepan, there is a native speaker who guides them in English studyclub and the English teachers have long experiences in teachingEnglish for young learner. It also makes students more interested inEnglish. To make the students enjoy and fun in learning English, theteachers must be able to select the appropriate strategies for teachingEnglish to them and know the characteristics of young learners inorder that it can help them in understanding the lesson andautomatically the goals of teaching and learning English can succeed.The purposes of this research are to investigate the strategies used bythe English teachers in teaching English at SMK Muhammad YaasiinSei Lepan Langkat, to investigate the reasons why the Englishteachers choose those strategies in teaching English at SMKMuhammad Yaasiin Sei, and to investigate the students’ responses ofteaching strategies applied in teaching English at SMK MuhammadYaasiin Sei Lepan. Research method, the reseacher used case studydesign with qualitative approach consisting of some data in the formof word, phrase and sentence. It is used to describe something that isknown to have happened in the process of teaching activity. Thereseacher also interviewed the English teacher and some students toget more information. Before doing the interview, the reseacher madethe interview guide. The reseacher conducted the three tehniques, theyare observation, interview and documentation.